Three-dimensional evaluation of soft tissue contour changes after premolar extraction with and without alveolar ridge preservation: A prospective observational study - Yun-Jeong Kim; Mi Young Lee; Jae-Eun Chung; Jang-Hyun Kim; Ji-Man Park; Ki-Tae Koo; Young Ku (PLoS ONE, 2026)
Background This prospective observational study evaluated three-dimensional soft tissue contour changes over a 90-day healing period following bilateral premolar extractions, with and without alveolar ridge preservation (ARP), using intraoral scanning and 3D digital analysis. Methods Eighteen orthodontic patients requiring bilateral premolar extractions were enrolled. In each patient, the extraction socket with relatively lower buccal bone height was assigned to alveolar ridge preservation (ARP), while the contralateral site was left to heal spontaneously. Intraoral scans were obtained immediately before extraction and at 30 days and 90 days post-extraction. Linear horizontal soft tissue changes were measured at 2 mm (H2) and 4 mm (H4) below the gingival margin, while vertical changes were assessed at the central aspect of the extraction socket. Surface displacement was analyzed using root mean square (RMS) distance, and volumetric changes were quantified using region-of-interest segmentation. Results Significant time-dependent changes in soft tissue contours were observed (p < .001), with greater horizontal reduction at H2 than H4, and more pronounced buccal changes (p < .05). At day 90, mean horizontal reduction at H2 buccal was 1.84 ± 0.69 mm (ARP) and 1.72 ± 0.68 mm (control); corresponding H2 lingual reductions were 1.34 ± 0.89 mm and 1.16 ± 0.29 mm. Vertical reduction peaked at 30 days with partial recovery by day 90. RMS-based displacement was greater buccally. Volumetric reduction was approximately 17% in both groups. No statistically significant differences were found between groups. Conclusions Intraoral scanning combined with digital superimposition proved effective for evaluating soft tissue changes after extraction. While ARP remains a valuable approach for alveolar bone preservation, its additional impact on soft tissue contour was limited in sites with favorable baseline conditions. Trial registration Clinical Research Information Service (CRIS), KCT0010923. Registered 19 August 2025. Retrospectively registered.